Anatomia do enraizamento adventício de estacas caulinares de Olea europaea L. - Martins, Mayron (2020)
Brazil is one of the largest importers of olive oil, due to the country's population size and insufficient national production of olives. In recent years, the national production of olives has started, in olive groves located in the south of the country and in the Serra da Mantiqueira. Due to the distinct climatic characteristics of these two regions, especially in relation to the Mediterranean, cultivars for exploration are distinct and, until now, few produce fruit regularly, mainly in the subtropical regions of Serra da Mantiqueira. Another limiting factor for the expansion of olive cultivation is the production of seedlings on a large scale, given that the olive cultivars that have been used in Brazil have low rooting capacity for their cuttings. In this sense, the objective of this work was to analyze, from a phytotechnical and anatomical perspective, the adventitious rooting in semi-hardwood stem cuttings of different cultivars of Olea europaea L.. For this purpose, we analyzed phytotechnical and anatomical characteristics of semi hardwood cuttings from four cultivars olive trees treated with IBA (3000 ppm) and maintained on vermiculite substrate in an intermittent nebulization chamber for a 60-day experimental period. The place of origin of the early roots was verified. The percentage of rooting and callogenesis of the cuttings, the thickness of phloem and cortex, as well as the thickness and spacing of the sclerenchyma ring were evaluated. The correlation between phytotechnical and anatomical characteristics was also assessed. Histochemical tests were carried out to detect the presence of phenolic compounds in the wound region of the cuttings. The cultivars showed different responses regarding the rooting percentage, with the Santa Catalina cultivar having the highest percentage of rooted cuttings and the lowest percentage of hardened cuttings when compared to the other cultivars. Thicknesses of cortex, phloem and sclerenchyma ring, as well as the spacing of this structure do not influence the rooting process. There was a strong and negative correlation between the percentages of rooted cuttings and hardened cuttings. Phenolic compounds were detected in exchange cells. The different responses among olive cuttings about adventitious rooting demonstrate that the cultivars have different requirements for influential factors in this process. This process is not directly influenced by anatomical structures, which are just more obstacles to be overcome by the newly formed root when emerging. The higher the percentage of callogenesis, the lower the percentage of rooted cuttings. The presence of compounds in the basal region of the cuttings is confirmed and attention is paid to the presence of phenolic compounds in cambium cells, the place of origin of the early roots in cuttings of the studied cultivars, since these are related to the synthesis of auxin.